Prognostic molecular markers in cancer – quo vadis?. Issue 3 (9th July 2013) - Søland, Tine M; Brusevold, Ingvild J
Abstract : Despite the tremendous number of studies of prognostic molecular markers in cancer, only a few such markers have entered clinical practise. The lack of clinical prognostic markers clearly reflects limitations in or an inappropriate approach to prognostic studies. This situation should be of great concern for the research community, clinicians and patients. In the present review, we evaluate immunohistochemical prognostic marker studies in oral squamous cell carcinomas (OSCC) from 2006 to 2012. We comment upon general issues such as study design, assay methods and statistical methods, applicable to prognostic marker studies irrespective of cancer type. The three most frequently studied markers in OSCC are reviewed. Our analysis revealed that most new molecular markers are reported only once. To draw conclusions of clinical relevance based on the few markers that appeared in more than one study was problematic due to between‐study heterogeneity. Currently, much valuable tissue material, time and money are wasted on irrelevant studies.